KEMANDIRIAN DAN PEMBERDAYAAN EKONOMI BERBASIS PESANTREN (Studi Kasus pada Pesantren al-Amanah Junwangi Krian) - Sugiono, Mohammad Arif Agus; Indrarini, Rahma (Universitas Negeri Surabaya, 2021)
Pesantren can't be separated from its contibution to educate society, an organization in which was established to be the center of education, religion, culture, and people's economy. Pesantren is one of the empowering institutions and to empower people. This research aims to indentify the potential in pesantren as an independent institution economically and is able to empower people economically. The method used in this research is descriptive qualitative method by using case study approach. The data collection techinques used were interview, observation, and documentation. The concept of modern independent pesantren of Al-Amanah Junwangi was institutional potential optimization of pesantren itself, without ignoring the concept of pesantren which holds independence in educationg the students. Pesantren is not actually a profit organization, but it can develop itself and provide economical impacts towards people and its surroundings. Strong institutional value in economy gives courage and motivation for its internal society to stand independent econimically. The concept of independence and economic empowerement in pesantren has surely lacknesses because of non-competent Human Resource in its field. However, sustainable evaluation and improvement can be an example of how non-economic organization can empower itself and empowering its surrounding.